KAJIAN METODE KONTEKSTUAL PAULUS “MENJADI SEPERTI” MENURUT I KORINTUS 9:19-23 SEBAGAI IMPLEMENTASI KARAKTER MISIONARIS - Pattinaja, Aska Aprilano; Kiamani, Andris; Loisoklay, Pulela Dewi (Sekolah Tinggi Teologi Hagiasmos Mission, 2024)
Evangelism has transcended ethnic and linguistic boundaries. The evangelistic movement has become very widespread, reaching neglected areas. Although there are studies that have discussed cross-cultural evangelism methods, the researcher found that there has not been a comprehensive discussion of the contextual methods used by Paul relating to the character of missionaries. That is why this research article discusses Paul's contextual method of